'I Get More in Contact with My Soul': Gang Disengagement, Desistance and the Role of Spirituality. (April 2020) - Deuchar, Ross
This article explores the links between gangs, masculinity, religion, spirituality and desistance from an international perspective. It presents insights from life history interviews conducted with a small sample of 17 male reforming gang members in Denmark who had become immersed in a holistic spiritual intervention programme that foregrounded meditation, yoga and dynamic breathing techniques. Engagement with the programme enabled the men to begin to perform broader versions of masculinity, experience improved mental health and well-being and develop a greater commitment to criminal desistance. Links with religious and spiritual engagement are discussed, and policy implications for the UK gang context included.